The genus Euhybus Coquillett (Diptera: Hybotinae) from China, with descriptions of five new species - Li, Meilin; Wang, Jingyu; Yang, Ding (Zootaxa, 2024)
Twelve species of the genus Euhybus are now known from Chine, including five species described as new to science: Euhybus basiflavus sp. nov., E. furcatus sp. nov., E. tenuifemur sp. nov., E. wuyishananus sp. nov. and E. yunnanensis sp. nov. All species are provided with diagnoses and distributions. Five new species are also provided with detailed descriptions and color illustrations. A distribution map and an identification key to all Chinese species of Euhybus are also provided.